43.6k views
0 votes
(12a^(2) - 3)/(2)*(2a + 1)^(-2)*((6)/((2a + 1)))^(-1)

User Ezgar
by
5.8k points

2 Answers

2 votes

Answer:

The answer is 2a-1/4

Explanation:

User Anju Aravind
by
5.5k points
5 votes

Answer:


\frac{144a^(4)+144a^(3) - 36 - 12a} {2a+1}\\

Explanation:


((12a^2-3))/(2*(2a+1)^(-2))*(6)/((2a+1)^(-1) )\\ = ((12a^2-3))/(2 * (1)/((2a+1)^(2) )) * (6)/((1)/(2a+1)  )\\ =((12a^2-3)(2a+1)^(2))/(2) * (6)/(2a+1)\\=((12a^2-3)(2a+1)^(2))/(2) * (6)/(2a+1)


= ((12a^2-3)(4a^(2) + 1 + 2 (2a)(1)))/(2) * (6)/(2a+1)\\= ((12a^2-3)(4a^(2) + 1 + 4a))/(2) * (6)/(2a+1)\\= ((12a^2-3)(4a^(2) + 1 + 4a))/(1) * (3)/(2a+1)\\= \frac{3(12a^2-3)(4a^(2) + 1 + 4a)} {2a+1}\\\\= \frac{3(12a^2(4a^(2) + 1 + 4a) - 3 (4a^(2)+1+4a)} {2a+1}\\= \frac{3(48a^(4)+12a^(2)+48a^(3)  - 12a^(2) -12 - 4a)} {2a+1}\\= \frac{144a^(4)+36a^(2)+144a^(3)  - 36a^(2) - 36 - 12a)} {2a+1}


= \frac{144a^(4)+36a^(2)+144a^(3)  - 36a^(2) - 36 - 12a} {2a+1}\\= \frac{144a^(4)+144a^(3) - 36 - 12a} {2a+1}\\

User AxelWass
by
6.3k points